Classification of Suspended Government Industries and their Geographical Distribution in Nineveh and Salah al-Din Governorates according to Types of Industrial Production and Spatial Location - Hassan Al-Azzawi, Diana Tariq; Attia Al-Jubouri, Noman Hussein (Journal of Tikrit University for Humanities, 2024)
Examining the industrial structure in relation to the factors influencing the spatial variations and distribution patterns of industrial facilities is a crucial topic in geographical research. This analysis holds economic significance as it contributes to the production of industrial goods to meet local market demands, creates employment opportunities, and helps alleviate unemployment. Additionally, it enhances the quality of life for its employees and generates economic benefits for the local area. Furthermore, it emphasizes the need of scrutinizing the industrial framework by unveiling the inherent characteristics of the industrial operations present in the Nineveh and Salah al-Din governorates. Hence, the researcher conducts a comprehensive examination of the halted government industrial facilities within Nineveh and Salah al-Din governorates using a field survey. This study aims to examine the geographical distribution of industrial facilities in the governorates of Nineveh and Salah al-Din, as well as the characteristics of their production activities prior to cessation.